2002
DOI: 10.1107/s0108767301017986
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state structure by time-resolved X-ray diffraction

Abstract: X-ray crystallography has traditionally been limited to the study of the groundstate structure of molecules and solids. 2À ], performed at helium temperatures with synchrotron radiation. The shortening of the PtÐPt bond by 0.28 (9) A Ê upon excitation is compatible with the proposed mechanism involving promotion of a PtÐPt antibonding d'* electron to a weakly bonding p orbital. The contraction is accompanied by a 3 molecular rotation. The time-resolved diffraction technique described here is applicable to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
131
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 19 publications
11
131
0
Order By: Relevance
“…8% of the GS value), while the distance between P planes was found to be almost unperturbed, thus implying a slight lengthening of the Pt-P bond in the 3 A 2u ES. Interestingly, the Pt-Pt bond contraction found by TR-XXS is less severe when compared to the 0.28 Å value obtained using ultrafast photocrystallography [211,212]. It is noteworthy that the same system was further studied in a Pt L 3 -edge TR-XAS experiment.…”
Section: (C) the Solution-phase Photochemistry Of The Transition Metamentioning
confidence: 99%
See 1 more Smart Citation
“…8% of the GS value), while the distance between P planes was found to be almost unperturbed, thus implying a slight lengthening of the Pt-P bond in the 3 A 2u ES. Interestingly, the Pt-Pt bond contraction found by TR-XXS is less severe when compared to the 0.28 Å value obtained using ultrafast photocrystallography [211,212]. It is noteworthy that the same system was further studied in a Pt L 3 -edge TR-XAS experiment.…”
Section: (C) the Solution-phase Photochemistry Of The Transition Metamentioning
confidence: 99%
“…Previous reports highlighted a 3 A 2u -symmetry lowest-lying triplet state [204,205], with a measured lifetime of 9.8 µs in deoxygenated water [206][207][208] and a quantum yield of approximately 100% [208]. The geometry of such a long-lived triplet state was thoroughly investigated in the crystal phase using both ultrafast [209][210][211] and stationary-state X-ray methods [212,213]. The crucial structural parameter is the contraction of the Pt-Pt bond distance, which , from analysis of TR-XXS data collected at 100 ps and 1 µs after laser excitation at 267 nm [199].…”
Section: (C) the Solution-phase Photochemistry Of The Transition Metamentioning
confidence: 99%
“…33 In 2002, Coppens et al reported 2.913 ¡ shortening (tetraethylammonium salt) in the excited triplet state by using the time-resolved pumpprobe X-ray diffraction method and density functional theory. 34,35 In 2002 and 2003, Ozawa, Toriumi, and Ohashi reported 2.9422.973 ¡ shortening (several organic counter ions) by using photostationary diffraction method. 36,37 Even though their data collection strategies are different, they clarified a similar photoexcited triplet state structure.…”
Section: Step I: Crystal Packing Approachmentioning
confidence: 99%
“…In contrast, with the advance of X-ray synchrotron sources that can generate high-flux, ultrashort X-ray pulses, time-resolved X-ray diffraction (scattering) and absorption techniques have become general and powerful tools to explore structural dynamics of matters. Accordingly, the techniques have been successfully applied to studying various dynamics of chemical and biological systems (Coppens, 2003;Coppens et al, 2004;Ihee, 2009;Ihee et al, 2005b;Kim et al, 2002;Schotte et al, 2003;Srajer et al, 1996;Techert et al, 2001;Tomita et al, 2009) and of condensed matters Cavalleri et al, 2006;Collet et al, 2003;Fritz et al, 2007;Gaffney et al, 2005;Lee et al, 2005;Lindenberg et al, 2005). On one hand, time-resolved X-ray diffraction enables us to access to the mechanism of structural transformations at the atomic level in crystalline state (Collet et al, 2003;Schotte et al, 2003;Srajer et al, 1996;Techert et al, 2001).…”
Section: Introductionmentioning
confidence: 99%